TPACK Competence and Technology Use Among in-Service EFL Teachers - Sukarni, Semi; Chasanah, Zulia; Maskuri, Edi Sunjayanto; Laksono, Puji; Anua Jah, Nurain Jantan (Universitas Pendidikan Mandalika, 2025)
In the context of teacher professionalism, the ability to effectively integrate technology into teaching practices is now part of the basic competencies that must be possessed. One of the conceptual frameworks that are widely used to measure and assess this competency is Technological Pedagogical and Content Knowledge (TPACK). Therefore, this study aims to (1) describe how in-service English teachers integrate technology into their EFL teaching, and (2) explain the perceptions of these teachers regarding their TPACK competency. The research is a mixed-method study that combines quantitative and qualitative data collection using observation and questionnaires. Thirty teachers consisting 11 male and 19 female involved in this study.Â The quantitative data were analyzed using descriptive analyses, while the qualitative data were analyzed using thematic analysis by presenting themes and codes. Â The finding of the study shows that in-service English teachers have